2016
DOI: 10.1002/qj.2731
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms producing different precipitation patterns over north‐eastern Italy: insights from HyMeX‐SOP1 and previous events

Abstract: During the first HyMeX Special Observation Period (SOP1) field campaign, the target site of north‐eastern Italy (NEI) experienced a large amount of precipitation, locally exceeding the climatological values and distributed among several heavy‐rainfall episodes. In particular, two events that occurred during the last period of the campaign drew our attention. These events had common large‐scale patterns and a similar mesoscale setting, characterised by southerly low‐level flow interacting with the Alpine orogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 58 publications
1
58
0
Order By: Relevance
“…The three selected cases are: 14-16 September 2006 (Chievolis), 30 October-2 November 2010 (Vicenza) and 10-12 November 2012 (Piancavallo). For the last two cases, a more detailed description can be found in Davolio et al (2016). Chievolis event occurred in the Friuli Venezia Giulia (FVG) region in late summer and was characterized by convective precipitation exceeding 300 mm in 24 h. The other two cases (Piancav- allo and Vicenza), occurred in autumn, were responsible for floods and affected both FVG and Veneto regions with orographic rainfall up to 250 and 300 mm in 24 h, respectively (Fig.…”
Section: Overview Of the Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three selected cases are: 14-16 September 2006 (Chievolis), 30 October-2 November 2010 (Vicenza) and 10-12 November 2012 (Piancavallo). For the last two cases, a more detailed description can be found in Davolio et al (2016). Chievolis event occurred in the Friuli Venezia Giulia (FVG) region in late summer and was characterized by convective precipitation exceeding 300 mm in 24 h. The other two cases (Piancav- allo and Vicenza), occurred in autumn, were responsible for floods and affected both FVG and Veneto regions with orographic rainfall up to 250 and 300 mm in 24 h, respectively (Fig.…”
Section: Overview Of the Eventsmentioning
confidence: 99%
“…Heavy precipitation over the Alps is directly (e.g., by orographic uplift) or indirectly (e.g., by orographic cyclogenesis) related to the influence of mountain ranges on atmospheric motions. Heavy precipitations over NEI are often associated with Sirocco or Bora winds (Manzato, 2007;Davolio et al, 2015Davolio et al, , 2016, thus involving intense air-sea interactions. In this situation, the Adriatic Sea acts as a source of moisture and heat for the atmosphere and contributes to destabilize the air mass in the boundary layer (PBL), which is then transported toward the mountains where convective instability is released.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (e.g. Buzzi and Foschini, 2000;Davolio et al, 2016) have shown that the largest component of the mountain-rangescale precipitation appears to be due to the orographic lifting of moist and impinging low-level flows. Consequently, the vertical uplifts forced by the Dinaric Alps area were favourable for the initiation and maintenance of convection.…”
Section: Iop4mentioning
confidence: 95%
“…Additional details on the synoptic situation are described in Ferretti et al (2014) and Davolio et al (2016). More rainfall was recorded on rain gauges on the north-eastern Adriatic coast.…”
Section: Iop19mentioning
confidence: 99%
“…The prediction of Heavy Precipitation Events (HPEs) that typically strike the western Mediterranean region by late summer (Lee et al, 2016;Davolio et al, 2016) is still a challenge for current Numerical Weather Prediction (NWP) models. Under a weak synoptic forcing, the location and time of the triggered convective cells is determined by mesoscale temperature and humidity inhomogeneities that define unstable regions prone to lifting.…”
Section: Introductionmentioning
confidence: 99%